Schooling Jim Crow : The Fight for Atlanta's Booker T. Washington High School and the Roots of Black Protest Politics - Driskell, Jay Winston, 1973- (Book collections on Project MUSE., 2014)
"This book describes how the early NAACP successfully organized a voting bloc in 1920s Atlanta powerful enough to force the city to build its first publicly funded Black high school"--Provided by publisher.